The Long History of “Doublethink”: A Response to Djelal Kadir’s “Agnotology and the Know-Nothing Party: Then and Now” - Broncano Rodríguez, Manuel (Review of International American Studies, 2017)
Manuel Broncano Rodríguez Texas A&M International University The Long History of “Doublethink”: A Response to Djelal Kadir’s “Agnotology and the Know-Nothing Party: Then and Now” A Response to Djelal Kadir’s “Agnotology and the Know-Nothing Party: Then and Now.” (In the present issue of RIAS). Keywords: humanities, state control, ignorance, American Literature, World Literature, world culture, American Studies, Comparative Studies